2014
DOI: 10.1111/jicd.12089
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament stem cells: an update and perspectives

Abstract: Chronic periodontitis is a serious infectious and inflammatory oral disease of humans worldwide. Conventional treatment modalities are effective for controlling periodontal disease. However, the regeneration of damaged periodontal tissues remains a major challenge in clinical practice due to the complex structure of the periodontium. Stem cell-based regenerative approaches combined with the usage of emerging biomaterials are entering a new era in periodontal regeneration. The present review updates the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 101 publications
(184 reference statements)
0
17
0
Order By: Relevance
“…Since the isolation and identification of multipotent postnatal stem cells from human PDL tissue 10 years ago (Seo et al 2004), these cells, defined as PDLSCs, have become an interesting adult stem cell source for regenerative dentistry because of their ease of isolation from discarded or removed teeth, particularly those teeth extracted for impaction or orthodontic reasons (Chamila Prageeth Pandula et al 2014;Bright et al 2015). Furthermore, these cells can differentiate into osteoblasts, chondrocytes, neurons and muscle cells, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the isolation and identification of multipotent postnatal stem cells from human PDL tissue 10 years ago (Seo et al 2004), these cells, defined as PDLSCs, have become an interesting adult stem cell source for regenerative dentistry because of their ease of isolation from discarded or removed teeth, particularly those teeth extracted for impaction or orthodontic reasons (Chamila Prageeth Pandula et al 2014;Bright et al 2015). Furthermore, these cells can differentiate into osteoblasts, chondrocytes, neurons and muscle cells, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these cells can differentiate into osteoblasts, chondrocytes, neurons and muscle cells, among others. PDLSCs are derived from ectomesenchymal origin, are formed during tooth development and have been investigated for the repair of tissues not only within but also outside the mouth (Chen et al 2012;Chamila Prageeth Pandula et al 2014). In particular, many preclinical and clinical studies have suggested that PDLSCs represent an effective therapeutic tool for periodontal regeneration (Bright et al 2015;Bassir et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal ligament stem cells (PDLSCs) represent a further plastic stem cell population within the human oral cavity [108]. Notably, their differentiation capacity is not only limited to mesenchymal derivatives as they are able to generate ectodermal progeny [109][110][111][112].…”
Section: Other Adult Stem and Progenitor Cellsmentioning
confidence: 99%
“…Lastly, like other MSC, PDLSC also show paracrine induction of angiogenesis in vitro and in vivo [32] . Thus, in addition to their multilineage potential, the possibility of an immortal cell line has made PDLSC highly promising for tissue engineering applications [5] .…”
Section: Background and Applicationsmentioning
confidence: 99%
“…MSC among craniomaxillofacial sources are diverse, unique and variably well characterized. These include dental pulp stem cells (DPSC) [4] , periodontal ligament stem cells (PDLSC) [5] , suture-derived mesenchymal stromal cells (SMC) [6] and gingival mesenchymal stem cells (GMSC) [7] ( Figure 2). …”
Section: Introductionmentioning
confidence: 99%